Experimental study of a water source heat pump (WSHP): evaluation of R32 refrigerant as a direct replacement for R410A - Belman Flores, Juan Manuel; Perez García, Vicente; Meza Enriquez, María Fernanda; Machado, Luiz (Acta Universitaria, 2026)
The energy performance of a water-source heat pump in heating mode was experimentally evaluated using R32 as a direct replacement for R410A. For this purpose, an experimental bench was constructed to simulate the operating conditions of the water source (water-glycol mixture) flow rate and temperature, as well as the set-point condition (space-heating temperature). These conditions expand on the existing literature, positioning R32 as a viable option in the short- and medium-term. The results indicated that R32 outperformed R410A, achieving COP increases of up to 40%. For set-point temperatures of 31 °C and 28 °C, the pump achieved 37% energy savings with R32 compared to R410A. Finally, a TEWI analysis was performed, where R32 showed an 84.2% reduction in indirect emissions due to lower energy consumption.